Cardiovascular toxicity of tyrosine kinase inhibitors during cancer treatment: Potential involvement of TRPM7 - Liu, Qing; Li, Suyao; Qiu, Yuran; Zhang, Jiayu; Rios, Francisco J.; Zou, Zhiguo; Touyz, Rhian M. (Frontiers in Cardiovascular Medicine, 2023)
Receptor tyrosine kinases (RTKs) are a class of membrane spanning cell-surface receptors that transmit extracellular signals through the membrane to trigger diverse intracellular signaling through tyrosine kinases (TKs), and play important role in cancer development. Therapeutic approaches targeting RTKs such as vascular endothelial growth factor receptor (VEGFR), epidermal growth factor receptor (EGFR), and platelet-derived growth factor receptor (PDGFR), and TKs, such as c-Src, ABL, JAK, are widely used to treat human cancers. Despite favorable benefits in cancer treatment that prolong survival, these tyrosine kinase inhibitors (TKIs) and monoclonal antibodies targeting RTKs are also accompanied by adverse effects, including cardiovascular toxicity. Mechanisms underlying TKI-induced cardiovascular toxicity remain unclear. The transient receptor potential melastatin-subfamily member 7 (TRPM7) is a ubiquitously expressed chanzyme consisting of a membrane-based ion channel and intracellular α-kinase. TRPM7 is a cation channel that regulates transmembrane Mg2+ and Ca2+ and is involved in a variety of (patho)physiological processes in the cardiovascular system, contributing to hypertension, cardiac fibrosis, inflammation, and atrial arrhythmias. Of importance, we and others demonstrated significant cross-talk between TRPM7, RTKs, and TK signaling in different cell types including vascular smooth muscle cells (VSMCs), which might be a link between TKIs and their cardiovascular effects. In this review, we summarize the implications of RTK inhibitors (RTKIs) and TKIs in cardiovascular toxicities during anti-cancer treatment, with a focus on the potential role of TRPM7/Mg2+ as a mediator of RTKI/TKI-induced cardiovascular toxicity. We also describe the important role of TRPM7 in cancer development and cardiovascular diseases, and the interaction between TRPM7 and RTKs, providing insights for possible mechanisms underlying cardiovascular disease in cancer patients treated with RTKI/TKIs.